The turn to the self: From “Big Character Posters” to YouTube videos - Li, Henry (Routledge, 2009)
This paper explores the process by which user-created content in contemporary China has evolved from being appropriated as a weapon of political mobilization and accusation to serving as a vehicle of independent self-representation. The analysis is set in the context of the social, political and economic metamorphosis that China has undergone in the past five decades and foregrounds the dynamics of political, economic and technological forces transforming Chinese media. The metaphor of “the wall” is used to chart the contours of the struggle for self-expression and representation. The paper concludes with a brief discussion of the political and social implications of the Internet and networked user created media content for China.